Beam angle selection incorporation of anatomical heterogeneities for pencil beam scanning charged-particle therapy. (23rd November 2016) - Toramatsu, Chie; Inaniwa, Taku
Abstract: In charged particle therapy with pencil beam scanning (PBS), localization of the dose in the Bragg peak makes dose distributions sensitive to lateral tissue heterogeneities. The sensitivity of a PBS plan to lateral tissue heterogeneities can be reduced by selecting appropriate beam angles. The purpose of this study is to develop a fast and accurate method of beam angle selection for PBS. The lateral tissue heterogeneity surrounding the path of the pencil beams at a given angle was quantified with the heterogeneity number representing the variation of the Bragg peak depth across the cross section of the beams using the stopping power ratio of body tissues with respect to water. To shorten the computation time, one-dimensional dose optimization was conducted along the central axis of the pencil beams as they were directed by the scanning magnets. The heterogeneity numbers were derived for all possible beam angles for treatment. The angles leading to the minimum mean heterogeneity number were selected as the optimal beam angle. Three clinical cases of head and neck cancer were used to evaluate the developed method. Dose distributions and their robustness to setup and range errors were evaluated for all tested angles, and their relation to the heterogeneity numbers was investigated. The mean heterogeneity number varied from 1.2 mm–10.6 mm in the evaluated cases. By selecting a field with a low mean heterogeneity number, target dose coverage and robustness against setup and range errors were improved. The developed method is simple, fast, accurate and applicable for beam angle selection in charged particle therapy with PBS.